Hydrography and Coastal Circulation along the Halifax Line and the Connections with the Gulf of St. Lawrence. Issue 3 (26th May 2016) - Dever, M.; Hebert, D.; Greenan, B.J.W.; Sheng, J.; Smith, P.C.
ABSTRACT: Acoustic Doppler Current Profilers and underwater gliders were simultaneously deployed as part of the Ocean Tracking Network to continuously monitor the Halifax Line (HL) and the Nova Scotia Current (NSC) between 2008 and 2014. The HL transects the Scotian Shelf, which connects dynamically important areas, such as the Grand Banks, the Gulf of Maine, and the Gulf of St. Lawrence (GSL). The oceanographic measurements made at the HL during this period provide a unique opportunity to study the temperature, salinity, and alongshore current conditions and variability at both seasonal and interannual time scales. The analysis of observations reveals that the water over the Scotian Shelf is mainly composed of water coming from the Gulf of St. Lawrence (Cabot Strait subsurface water) in the upper layer (30 to 50 m, 81%) and Warm Slope Water below 100 m (77%), highlighting the connectivity between the GSL and the Scotian Shelf. The temperature–salinity characteristics of the Cold Intermediate Layer (CIL) observed along the HL and located mainly between 50 and 100 m, is indistinguishably influenced by both water coming from the Inshore Branch of the Labrador Current and CIL water formed in the GSL. These proportions stay similar over interannual time scales, suggesting that the 2012 warm anomaly observed over the Scotian Shelf is primarily driven by the advection of already anomalously warm water coming from offshore regions. The analysis of glider data also reveals that most of the alongshore transport over the Scotian Shelf occurs within the first 60 km from the coast, where the NSC is located. It was found that the freshwater discharge from the St. Lawrence River at Québec and the alongshore transport across the NSC have a significant covariance at a 9-month lag. The Empirical Orthogonal Function (EOF) analysis demonstrates that most of the current variability (between 78 and 92%) can be explained by the first EOF, which represents the baroclinicity resulting from the freshwater outflow coming from the GSL. Part of the second EOF is associated with the local wind forcing and explains between 4 and 14% of the NSC variability.